Healthcare worker practices for HPV vaccine recommendation: A systematic review and meta-analysis - Damola Bakare; Elisa Gobbo; Kofoworola O. Akinsola; Ayobami A. Bakare; Julius Salako; Claudia Hanson; Sibylle Herzig van Wees; Adegoke Falade; Carina King (Human Vaccines & Immunotherapeutics)
Healthcare workers (HCWs) are trusted sources of information for vaccination and their attitude toward vaccination is thus critical. We aimed to synthesize existing literature on healthcare workers’ HPV vaccine confidence and their practices of recommending this vaccine. We conducted a systematic literature review and meta-analysis, with the search conducted last in March 2024. For the inclusion criteria, the studies needed to include healthcare worker practices or behaviors on recommending the HPV vaccination. Seventy-three articles were included. The proportions of HCWs recommending varied considerably by region and gender of the recipient, but there was no statistically significant difference in income level or pre- or post-HPV vaccine introduction into the national vaccination program. The main barriers to recommending HPV vaccination were concerns around safety and efficacy, cost, parental concerns, and systemic barriers. The results illustrate the importance of contextually adapted approaches to improving vaccine acceptance and recommendation.